Multicultural libraries - Alentejo, Eduardo; Señorans, Rodrigo; Matos, Elesbão (Qualitative and Quantitative Methods in Libraries; Vol 7 No 1 (2018): March 2018 Issue, 2019)
It reports some findings from the research project in progress about multicultural public libraries in Brazil. Under the National Policy for the Sustainable Development of Traditional Peoples and Communities, this research studies cultural diversity of traditional human groups in the context of Brazilian public libraries. Through literature review and mapping of multicultural public libraries in the country, it aims to analyze how social values of Quilombola, Indigenous and Gypsy communities are being included in Brazilian public libraries. As main result, it explains that public libraries are changing their services to embrace multiculturalism. About 80% of Brazilian public libraries found in this study had become multicultural. It concludes that public libraries in Brazil are becoming cultural artefact guided to the culture diversity to serve society.